In silico's study of Ketepeng leaf (Cassia alata L.) as inhibitor of aspartic protease from Boophillus microplus as a natural acaricide of ticks in cattle - Purwono, R. M.; Miftahurridho, Z.; Safitri, M.; Supriyono, S.; Yusriani, R.; Prasetyo, B. F. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
The objective of this study was to evaluate the potential of Cassia alata L. leaf extract as an anti-tick agent through molecular docking analysis against the aspartic protease enzyme from Ixodes ricinus (IrCD1). The study aimed to identify natural compounds that could serve as safer alternatives to syn-thetic acaricides for controlling Boophilus microplus, a major ectoparasite affecting cattle.The research utilized an in silico approach, employing molecular docking techniques to assess the binding affinity of 14 secondary metabolites from Cassia alata leaves against IrCD1. The receptor structure (PDB ID: 5N7Q) was obtained from the Protein Data Bank, while ligand structures were sourced from PubChem and KNApSAcK. The docking process was performed using YASARA Structure, with binding free energy (ΔG) and dissociation constant (Kd) values analyzed for ligand-receptor interactions. Addition-ally, the bioavailability of the selected compounds was assessed using Lipinski’s Rule of Five. The results identified four key metabolites—chrobisiamone A, chrysophanol, quercetin, and rhein—as the most promising inhibitors, with binding free energy values lower than the native ligand, pepstatin. Chrobisiamone A demonstrated the strongest interaction with IrCD1, indicating its potential as a potent acaricidal compound. The study also found that these compounds exhibit strong hydrogen bonding and hydrophobic interactions at the receptor’s active site, enhancing their inhibitory potential. In conclu-sion, the findings support the potential development of organic acaricides derived from Cassia alata L. leaves, with chrobisiamone A emerging as a promising candidate. Further in vitro and in vivo studies are needed to validate its efficacy and safety in tick control applications.